2015
DOI: 10.1016/j.jiac.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

A characteristic of polymorphic membrane protein F of Chlamydia trachomatis isolated from male urogenital tracts in Japan

Abstract: Although sexually transmitted disease due to Chlamydia trachomatis occurs similarly in both men and women, the female urogenital tract differs from that of males anatomically and physiologically, possibly leading to specific polymorphisms of the bacterial surface molecules. In the present study, we therefore characterized polymorphic features in a high-definition phylogenetic marker, polymorphic outer membrane protein (Pmp) F of C. trachomatis strains isolated from male urogenital tracts in Japan (Category: Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Interestingly, accumulating evidence has shown that among the nine Pmp families (A through I) expressed by C. trachomatis , PmpF is a high-definition phylogenetic marker that is strongly affected by host-selective pressures, such as those exerted by the microbial flora ( 7 9 ). In fact, we have recently demonstrated that PmpF of C. trachomatis isolated from the urogenital tracts of Japanese males showed less genetic diversity than the same protein isolated from the genital tracts of Japanese females, raising the idea that genetic diversity among C. trachomatis strains may be dependent on sexual differentiation ( 10 ). We therefore sequenced C. trachomatis strain 54 ( ompA genotype B, accession number LC031846) isolated from the urogenital tract of a Japanese male.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Interestingly, accumulating evidence has shown that among the nine Pmp families (A through I) expressed by C. trachomatis , PmpF is a high-definition phylogenetic marker that is strongly affected by host-selective pressures, such as those exerted by the microbial flora ( 7 9 ). In fact, we have recently demonstrated that PmpF of C. trachomatis isolated from the urogenital tracts of Japanese males showed less genetic diversity than the same protein isolated from the genital tracts of Japanese females, raising the idea that genetic diversity among C. trachomatis strains may be dependent on sexual differentiation ( 10 ). We therefore sequenced C. trachomatis strain 54 ( ompA genotype B, accession number LC031846) isolated from the urogenital tract of a Japanese male.…”
Section: Genome Announcementmentioning
confidence: 99%